Uso De Dispositivos Intra Vaginales A Base De Progestágenos Para Acelerar El Inicio De La Vida Reproductiva En Novillas Cebú- Brahman En La Finca El Bolsillo, Departamento – Meta, Colombia - Escobar Huertas, Andersson Fabián; LLano Riveros, Diego (Universidad Antonio Nariño, 2023)
A progestogen-based intravaginal device is used that comes in the form of a T used to control the estrous cycle and helping the reproductive life of the animals, where estrus synchronization is included with the help of estrogens. This device will act by absorbing into the mucosa of the cow's vagina, thus in turn causing a blockage in the Hypothalamic - Pituitary axis, thus avoiding the occurrence of heat until the device is removed, in our environment this This device is used in some farms with the help of synchronization protocols in order to have a better reproductive index.